2020
DOI: 10.3390/ma13225300
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Multi-Stage Cold Forging of an SUS304 Ball-Stud with a Hexagonal Hole at One End

Abstract: SUS304 stainless steel is characterized by combined tensile and compression testing, with an emphasis on flow stress at higher strain and temperature. The plastic deformation behavior of SUS304 from room temperature to 400 °C is examined and a general approach is used to express flow stress as a closed-form function of strain, strain rate, and temperature; this is optimal when the strain is high, especially during automatic multi-stage cold forging. The fitted flow stress is subjected to elastothermoviscoplast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…[90] Copyright 2008, Elsevier). Byun et al [98] suggested the use of nonisothermal analysis of temperature effect for automatic cold forging of SUS304 ball-stud as it gave positive results on die wear and its fatigue characteristics.…”
Section: Forging Toolsmentioning
confidence: 99%
“…[90] Copyright 2008, Elsevier). Byun et al [98] suggested the use of nonisothermal analysis of temperature effect for automatic cold forging of SUS304 ball-stud as it gave positive results on die wear and its fatigue characteristics.…”
Section: Forging Toolsmentioning
confidence: 99%
“…The implicit elastoplastic finite element method with tetrahedral MINI-elements [ 4 , 8 , 37 ] was used to simulate the process. We assumed that the material obeyed von Mises yield criterion while the die parts were assumed rigid in simulating the forging process.…”
Section: Characteristics Of Cyclic Stresses On a Prestressed Diementioning
confidence: 99%
“…To the contrary, the high-cycle fatigue (HCF) life of die parts is of great importance in cold forging [ 2 ], especially during automatic multi-stage cold forging. Die fatigue life is becoming a major issue because complicated die structural analysis has become increasingly possible owing to recent advances in metal forming simulation technologies [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The strain up to which the flow stress was theoretically obtained was quite large. The technique can predict the flow stress at the strain of around 1.5, depending on the materials [ 33 , 34 , 35 ]. Note that the point marked “necking point” in the true stress-strain curve in Figure 6 corresponds to the actual necking point in Figure 7 .…”
Section: Problem Descriptionmentioning
confidence: 99%